Interventional strategies to reduce biological hazards in animal feed - Cochrane, Roger Andrew (Kansas State University, 2018)
Porcine epidemic diarrhea virus (PEDV) is a heat-sensitive virus that devastated the United States swine industry. Because of its heat sensitivity, it was hypothesized that a pellet mill mimicking commercial thermal processing may mitigate PEDV infectivity. From the results, it was determined that a conditioning time of 30 sec or greater and temperatures above 54.4°C were effective point-in-time kill steps to inactive PEDV in a research setting. However, this does not prevent subsequent recontamination after pelleting as it is a point-in-time mitigation step. To further explore this, various mitigation additives were evaluated to prevent or mitigate PEDV post-pellet contamination in swine feed and ingredients. Various additives were examined across 3 experiments and included mitigation additives of medium chain fatty acids (MCFA), organic acids (OA), essential oils (OA), formaldehyde based products, and sodium bisulfate. From Exp. 1, formaldehyde, medium chain fatty acids (MCFA), essential oils (EO), and organic acid (OA) each decreased detectable PEDV RNA compared to the control (P<0.05). Additionally, PEDV stability over time was influenced by matrix as the meat and bone meal and spray-dried animal plasma resulted in a greater (P<0.05) quantity of detectable PEDV RNA over 42 days compared to that of the swine diet and blood meal. In Exp. 2, the 1% MCFA inclusion was equally effective at mitigating PEDV as a commercially available formaldehyde product in the complete swine diet. To further explore the effects of MCFA against PEDV, Exp. 3 was conducted to evaluate lower inclusion levels of MCFA and fat sources containing MCFA. It was noted that formaldehyde, 1% MCFA (1:1:1: of caproic, caprylic, and capric acids), 0.66% caproic, 0.66% caprylic, and 0.66% capric acids enhance the RNA degradation of PEDV in swine feed as determined by a bioassay. The MCFA were also evaluated against Salmonella Typhimurium, Generic Escherichia coli, Enterotoxigenic Escherichia coli, and Campylobacter coli. It was noted that the efficacy of the MCFA varied between each bacteria species with caproic and caprylic being the most effective. Commercial developmental products were also tested and determined that Product A and B provided the lowest MIC values across Salmonella Typhimurium, Generic Escherichia coli, and Enterotoxigenic Escherichia coli (P < 0.05). Product A and B were further tested in an animal disease trial utilizing a strain of enterotoxigenic Escherichia. coli O149:K91: K88. From d 7 to 14, chlortetracycline, 1:1:1 blend, and Product B, all improved G:F compared to the control (P<0.05). This also led to chlortetracycline and Product B having an improvement (P<0.05) over the control diet from d 0 to 14. A treatment × day interaction for the enterotoxigenic E. coli plate scores was observed (P < 0.05), which occurred because of the decrease (P<0.05) in plate scores for Product B from d 1 to d 14 and an increase (P<0.05) in chlortetracycline from d 7 to 14. A decrease (P<0.05) in plasma urea nitrogen and haptoglobin was observed as time increased from d -2 to 14. In summary MCFA have shown to be an effect interventional mitigation strategy against PEDV and various bacteria.
Keywords: Medium chain fatty acids; Porcine epidemic diarrhea virus; Swine; Minimum inhibitory concentration; Fat source; Chlortetracycline